A Solution with Its Own Problems : Analysing the Problems Encountered by the â€œKampus Mengajarâ€ Program - Ramadansur, Rahmat; Bastian, Adolf; Rizky, Ramanda; Sembiring, Al Khudri; Herdi, Herdi; Derin, Tatum (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to highlight and evaluate the issues at an in-depth level to provide different solutions that are expected to be a reflection for the government, especially the Ministry of Education and Culture, to be able to improve the implementation and monitoring of the Kampus Mengajar Program. A descriptive qualitative approach was used, and the data were collected from a focus group discussion with students of the English Education Study Program at Universitas Lancang Kuning, then the data was analyzed descriptively. The results highlight some problems in the implementation of the Kampus Merdeka Program. These included a lack of coordination and clear communication between stakeholders, which led to confusion among students and schools, uneven targeting of schools, inadequate support for the program, and credit conversion, resulting in frustration and challenges. Addressing these issues, the study recommended increased socialization of the program, transparency in credit equivalency, and more accurate school data collection. In conclusion, this research offers several solutions that are expected to reflect the Ministry of Education, Culture, Research and Technology (Kemendikbudristek) that the Kampus Mengajar Program faces various challenges in its implementation, which need to be addressed for the program to effectively meet its goal of improving education in the 3T areas.